Didactic strategies in the production of narrative texts in Students of the III cycle - Ugel 03 – Lima - Hernández Oré, Hilda Giovanna (2023)
The objective of this scientific study is to demonstrate the influence of didactic strategies in the elaboration of narrative text in the student of the III cycle, I. E Hipólito Unanue from Cercado de Lima. Quantitative applicative approaches with a quasi-experimental design, sample made up of 52 students: 27 from the control group (CG) and 25 from the experimental group (EG). To collect data we used the survey, a pre-test and post-test were applied for text productions, checklists for the results of the tests, a learning session to apply the didactic strategies. According to the statistical result with p-value less than 0.05, we reject the null hypothesis. This indicates the existence of statistically significant differences between GC and GE in the post-test in narrative text production. It is concluded that applying a didactic strategy in writing processes improves the elaboration of narrative text in students of the III cycle, I.E 0040 Hipólito Unanue, so its application is necessary in the learning sessions that correspond to the competencies "They write diverse texts in their native language”, so that the student in the sample improves his level of story production.